2015
DOI: 10.1371/journal.pone.0120396
|View full text |Cite
|
Sign up to set email alerts
|

Large Genomic Fragment Deletions and Insertions in Mouse Using CRISPR/Cas9

Abstract: ZFN, TALENs and CRISPR/Cas9 system have been used to generate point mutations and large fragment deletions and insertions in genomic modifications. CRISPR/Cas9 system is the most flexible and fast developing technology that has been extensively used to make mutations in all kinds of organisms. However, the most mutations reported up to date are small insertions and deletions. In this report, CRISPR/Cas9 system was used to make large DNA fragment deletions and insertions, including entire Dip2a gene deletion, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 34 publications
3
93
0
1
Order By: Relevance
“…Although deletions of 65 kb have been generated by zygote injection previously (Zhang et al ., 2015), this is relatively small and the relationship between size and efficiency was unknown. We also wished to establish a reliable method for generating large duplications.…”
Section: Introductionmentioning
confidence: 96%
“…Although deletions of 65 kb have been generated by zygote injection previously (Zhang et al ., 2015), this is relatively small and the relationship between size and efficiency was unknown. We also wished to establish a reliable method for generating large duplications.…”
Section: Introductionmentioning
confidence: 96%
“…47,48,58 Introduction of 2 engineered nucleases can result in targeted deletion or inversion, duplication, local indels at nuclease cleavage sites, or translocations/ chromosomal rearrangements. [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Here, we review genome-editing approaches for genetic correction and disruption strategies for the b-hemoglobinopathies as summarized in Figure 1 and Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this system can be used to generate genetically modified mice rapidly by microinjecting sgRNAs with Cas9 into fertilized eggs [4,5,6,7,8,9]. Several studies have reported the induction of an efficient CRISPR/Cas9-mediated genomic rearrangement such as deletion or inversion of ~100 kb [10,11,12]. However, the maximum size of indels that can be induced by the CRISPR/Cas9 system is still unclear.…”
mentioning
confidence: 99%